Amplification and generation of short and ultrashort pulse from hafnium bismuth erbium co-doped fiber / Aminah Ahmad - Aminah , Ahmad (2021)
Compact optical amplifier, nonlinear fiber laser and pulse generation have been successfully demonstrated using hafnium-bismuth-erbium co-doped fiber (HB-EDF) as the gain medium. The HB-EDF was recently fabricated using a modified chemical vapour deposition (MCVD) process in conjunction with the solution doping (SD) technique. The fiber has an Erbium ions concentration of 12500 wt. ppm, which was realized due to the co-doping with Hafnium and Aluminum ions. Firstly, a flat gain amplifier operating was realized using 50 cm long HB-EDF at -10 dBm input signal. The amplifier’s gain varies from 9.3 to 9.8 dB with a noise figure less than 4.1 dB within a wavelength range from 1525 to 1555 nm. A BFL can be realized with 0.5 m long HB-EDF to generate a stable Stokes operating at wavelength 0.09 nm shifted from the Brillouin pump. Multiwavelength fiber laser combs have been successfully achieved by the deployment of an HB-EDF as a gain medium at room temperature. For instance, a Brillouin Erbium fiber laser with an eight-line comb with an average spacing of 0.087 nm was obtained at the 980 nm pump power of 75.3 mW. The multi-wavelength comb with a constant spacing of approximately 0.26 nm was also realized by making use of the four-wave mixing effect. Q-switched and mode-locked HB-EDFLs have also been successfully demonstrated using two different SAs: multi-layer BP and Bismuth-doped fiber. For instance, a stable Q-switched HB-EDFL was obtained with a triple wavelength operation using a backward pumping scheme in conjunction with BP SA. The stable multiwavelength optical pulses are achieved with repetition rates of 41.15- 60.83 kHz by adjusting pump power. The shortest pulse width of 6.06 μs and the maximum pulse energy of 12 nJ were obtained at 223 mW pump power. A dark pulse generation was also successfully demonstrated through a mode-locking operation in a fiber laser cavity with BDF as a SA and HB-EDF as a gain medium. The mode-locked operational wavelength was recorded to be 1531.95 nm, with the repetition rate of 1.1 MHz. The proposed fiber lasers a compact design since they used an ultra-short length of HB-EDF as the gain medium.